Biogenic gases and the oxidation and reduction of carbon in Amazon River and floodplain waters - Richey, Jeffrey E.; Devol, Allan H.; Wofsy, Steven C.; Victória, Reynaldo Luiz; Riberio, Maria N G (Limnology and Oceanography, 1988)
This article is in Free Access Publication and may be downloaded using the “Download Full Text PDF” link at right. © 1988, by the Association for the Sciences of Limnology and Oceanography, Inc.
Keywords: Biogenic Gases; Carbon; Carbon Oxidation; Carbon Reduction; Floodplain; Floodplain Water; Oxidation; River Water; Brazil, Amazon River; South America, Amazon River